Burnout among preschool teachers in Serbia. (30th September 2020) - Terzic-Supic, Z; Piperac, P; Maksimovic, A; Karic, S; Hacko, B; Todorovic, J
Abstract: Background: Pedagogical work has been one of the most stressful professions, especially work with pre-school children. Working with each age group has particular challenges, in which educators participate in the development of healthy lifestyles in children, their physical activity habits and their identity as social beings. The incidence of stress-related illnesses is more common among teachers than in the general population. The aim of this study was to examine the prevalence of burnout syndrome among preschool teachers in Serbia and factors associated with it. Methods: The cross-sectional study was conducted between October 2018 and April 2019 and included National representative sample of 482 pre-school teachers in Serbia. The study instrument consisted of four sections: the socio-demographic, lifestyle and workplace characteristics; Copenhagen Burnout inventory; Beck Depression Inventory, and Zung Anxiety Scale. Results: The average score on total burnout was 39.1±17.0, while the average score per scales on Copenhagen burnout inventory were: 41.3±18.7 for personal burnout, 41.2±15.9 for work-related burnout and 34.7±22.0 for client related burnout. The frequency of total burnout was 27.1%. Multivariate logistic regression analysis with total burnout as an outcome variable showed that being singe (OR: 0.18, 95% CI: 0.05-0.58), having poor (OR: 6.05, 95% CI: 1.05-34.91), or average (OR: 3.60, 95% CI: 1.57-8.25) self-rated health, not having didactic tools (OR: 2.71, 95% CI: 1.21-6.04), having higher score on Beck depression inventory (OR: 1.19, 95% CI: 1.09-1.29) or Zung anxiety scale (OR: 1.10, 95% CI: 1.03-1.18) was significantly associated with total burnout among our participants. Conclusions: Our study showed the worryingly high prevalence of burnout among preschool teachers in Serbia. The results indicate its association with mental health problems, depression and anxiety, and yield for preventive action. Key messages: There is a worryingly high prevalence of burnout among preschool teachers in Serbia. Total burnout was associated with mental health problems.